Modular smart home using WiFi technology - Yus Kamalrul, Mohamed Yunus (2019)
Malaysia is moving rapidly into Internet of Things (IoT) technology realm. This can be seen with MIMOS pilot projects such as Aquaculture Farming: From Pond to Plate, Continuous Health Monitoring, Smart Village: Lanchang and Intelligent Landfill Management. Modular Smart Home Using WiFi Technology is a project in respond towards the effort of Malaysia in IoT. Smart Home hardware and systems can be seen around the globe from Amazon Echo to Google Home and our home grown system, VYROX Smart Home but problems with these system is many functionality squeezed into one device in which user has no choice to add or remove functionality and if one tiny part of these system is faulty, user need to change the whole device including parts that is working in perfect condition. This project objective is to implement WiFi technology into smart home device, to implement a modular version of smart home device and to implement basic security measures into the smart home application.